1975
DOI: 10.1111/j.1432-1033.1975.tb04082.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Catabolite Repression in Escherichia coli K12 Mutants Defective in Methyl-alpha-d-Glucoside Transport

Abstract: 1. Two spontaneous Escherichia coli K12 mutants resistant to glucose catabolite repression were isolated using minimal agar plates with methyl a-D-glucoside. Mutants grow well on glucose and mannitol.2. Glucose does not inhibit the inducible enzyme synthesis in isolated mutants: mutant cell (in contrast to parent cells) produce high levels of j-galactosidase and L-tryptophanase under the conditions of glucose catabolite repression.3. The isolated mutants are negative in methyl-a-D-glucoside transport; glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In those cases, phosphorylation and transport of glucose, catalyzed by II-BGlc, are completely absent, even at high external concentrations. The pts-418 mutation is also different from the tgl mutation described by Gershanovitch and coworkers in E. coli (1,5). tgl mutants are still able to phosphorylate methyl a-glucoside, provided it can reach its phosphorylation site inside the cell.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In those cases, phosphorylation and transport of glucose, catalyzed by II-BGlc, are completely absent, even at high external concentrations. The pts-418 mutation is also different from the tgl mutation described by Gershanovitch and coworkers in E. coli (1,5). tgl mutants are still able to phosphorylate methyl a-glucoside, provided it can reach its phosphorylation site inside the cell.…”
Section: Discussionmentioning
confidence: 82%
“…Enzyme II-B('c could be composed of more than one subunit. ptsG might code for a protein that is involved in methyl a-glucoside phosphorylation, whereas a second gene might code for a protein which is responsible for transport per se (1,5,6). If those two genes are closely linked, introduction of the ptsG: :TnlO mutation would at the same time eliminate also the pts-418 mutation, which is responsible for the transport of glucose in AptsHI galP strains.…”
Section: Isolation Of "mentioning
confidence: 99%
“…Mutational events could possibly lead to altered enzymes II with dissociated phosphorylation and transport activities. For instance, Bourd et al and Erlagaeva et al (2,4) and Kornberg and Jones-Mortimer (8) have described mutations in E. coli, designated tgl, which impair methyl a-glucoside transport but allow normal phosphorylation of this sugar in sonic extracts or in cells made permeable by toluene treatment. On the other hand, we have described mutants of S. typhimurium in which the enzyme II specific for mannose and glucose may catalyze the facilitated diffusion of galactose in the absence of phosphorylation (15).…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors did not , obtain more structural information about the role of these proteins in the transport process. Bourd et al [30] reported in Escherichia coli the isolation of a mutant called tgl, defective in the transport of the a-methylglucoside, the mutation leaving the phosphotransferase activity undamaged. This mutant was isolated as resistant to x-methylglucoside-mediated catabolite repression.…”
Section: Discussionmentioning
confidence: 99%